Connecting expressions and verb phrases in the essay writing of first-year students : pedagogical implications for course design - Coetzer, Amanda (My University, 2019)
The aims of the study were to compare connector use and verb phrase use between two achievement groups. The achievement groups comprised the Highs, students whose essays were highly rated (124 essays; word length 59702), and the Lows, students whose essays were rated poorly (126 essays; word length 60524). The analytical frameworks for the analysis of appropriate use were taken from Biber, Johansson, Leech, Conrad and Finegan (1999).The analytical frameworks for inappropriate use were designed by the researcher. Connectors comprised circumstance adverbials, linking adverbials, co-ordinators and relativisers. Verb phrase uses comprised all the categories described in Biber, et al. (1999). The analysis entailed counting number of occurrences per use for each achievement group and determining whether difference in use was significant or not by undertaking Log Likelihood calculations using Paul Rayson’s Log Likelihood calculator available online. These also indicate the relative frequency of each use. The results for appropriate connector use revealed that although no significant differences occurred with respect to connector categories, highly/significant differences did occur with regard to specific forms. Regarding inappropriate connector use, results showed that differences between the two achievement groups were overall highly significant, with a substantially higher occurrence of inappropriate uses in the Lows compared to the Highs. The results for appropriate verb phrase use revealed highly/significant differences between the Highs and Lows for several verb phrase categories, such as modal auxiliary use and Perfect Aspect. The results for inappropriate verb phrase use, as was the case for inappropriate connector use, showed highly significant differences between the two achievement groups, with the Lows having a much higher incidence of inappropriate uses than the Highs. The study finally considers the pedagogical implications arising from the results and makes suggestions for course design relating to writing instruction.
Thesis (Ph.D. (English Studies)) -- University of Limpopo, 2019
Keywords: Connector use; Verb phrase; Essay writing; First-year students; English language -- Verb phrase; Grammar, Comparative and general -- Verb phrase